Influence of iodoform on antimicrobial potential of calcium hydroxide Influência do iodofórmio no potencial antimicrobiano do hidróxido de cálcio - Carlos Estrela; Cyntia Rodrigues de Araújo Estrela; Augusto César Braz Hollanda; Daniel de Almeida Decurcio; Jesus Djalma Pécora (University of São Paulo, 2006)
The purpose of this research was to verify the influence of Iodoform on antimicrobial potential of calcium hydroxide. S. aureus, E. faecalis, P. aeruginosa, B. subtilis, C. albicans were the biological indicators. The substances tested were: calcium hydroxide + saline; calcium hydroxide + Iodoform + saline; Iodoform + saline. For the agar diffusion test, 18 Petri plates with 20 ml of BHI agar were inoculated with the microbial suspensions. Fifty-four cavities were made and filled with the substances tested. The diameters of microbial inhibition were then measured. In direct exposure test, 162 #50 sterile absorbent paper points were immersed in the experimental suspensions for 5 min, and covered with the pastes. At intervals of 24, 48 and 72 hours, the paper points were immersed in 10 ml of Letheen Broth, followed by incubation at 37°°C for 48h. Microbial growth was evaluated by turbidity of the culture medium. A 0.1 ml inoculum obtained from the Letheen Broth was transferred to 7 ml of BHI, and incubated at 37°°C for 48h. Bacterial growth was again evaluated by turbidity of the culture medium. The calcium hydroxide associated with the saline or the iodoform plus saline showed antimicrobial effectiveness in both experimental methods. The iodoform paste presented antimicrobial ineffectiveness for the agar diffusion test on all biological microorganisms and for the direct exposure test on B. subtilis and on the mixture. Objetivo deste estudo foi verificar a influência do Iodofórmio no potencial antimicrobiano do hidróxido de cálcio. S. aureus, E. faecalis, P. aeruginosa, B. subtilis, C. albicans foram os indicadores biológicos. As substâncias testadas foram: hidróxido de cálcio + solução salina; hidróxido de cálcio + iodofórmio + solução salina; iodofórmio + solução salina. Para o teste de difusão em ágar, 18 placas de Petri contendo 20 ml de ágar BHI foram inoculadas com as suspensões microbianas. Cinqüenta e quatro cavidades foram feitas e preenchidas com as substâncias testadas. Os diâmetros da inibição microbiana foram então mensurados. No teste de exposição direta, 162 pontas de papel absorvente número 50 esterilizadas foram imersas nas suspensões experimentais por 5 minutos, e cobertas pelas pastas testadas. Em intervalos de 24, 48 e 72 horas, as pontas de papel foram imersas em 10 ml de Letheen Broth, seguido de incubação a 37°°C por 48 horas. O crescimento microbiano foi avaliado pela turvação do meio de cultura. Um inóculo de 0.1 ml obtido do Letheen Broth foi transferido para 7 ml de BHI, e incubado a 37°°C por 48h. o crescimento bacteriano foi novamente avaliado pela turvação do meio de cultura. As pastas contendo hidróxido de cálcio e solução salina, hidróxido de cálcio-iodofórmio e solução salina mostraram significativa atividade antimicrobiana nos métodos experimentais estudados. A pasta contendo iodofórmio e solução salina foi inefetiva pelo teste de difusão em agar e, também, por exposição direta, para o B. subtilis e a mistura.